Thermal Intelligent Control DVFS for Cyber-physical Systems - Hernandez Almudi, Pablo; Montijano, Eduardo; Suárez Gracia, Darío (Jornada de Jóvenes Investigadores del I3A, 2022)
This work explores the use of well-known control techniques to tackle the heat dissipation problem in embedded devices. These types of devices lack of good solutions for managing heat and the existing ones may lead to unpredictable performance variations. We will show a way of solving the problem with classic control theory and workload identification.